The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1007/bf02221129
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Aroclor® 1254 and its physiological activity in several estuarine organisms

Abstract: The occurrence of high concentrations of a PCB (Aroclor 1254) in the Pensacola estuary prompted field and laboratory studies by the Gulf Breeze Environmental Research Laboratory (EPA). Monitoring of the estuary indicates the chemical is present in all components--particularly in sediments and fishes. Residues appear to be diminishing in sediments. Toxicity tests show estuarine species sensitive at ppb concentrations in water, with a ciliate protozoan (Tetrahymena pyriformis W), (Fundulus similis), affected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The endothelial cells had a few short cytoplasmic extensions into the sinusoidal lumen, smoothcoated pinocytotic vesicles at the plasma membrane, and smooth-surfaced vesicles in the cytoplasm; however, none was seen that was rich the light microscope degenerative liver changes 2Martin Feed Mills, Elmira, Ontario. and lipid accumulation have been seen in two 3Generously supplied by Monsanto Canada Ltd., species of fish exposed to PCB's (13,37). in lysosomes, that had many cytoplasmic projections, or whose cytoplasm was protuberant into the sinusoidal lumen, criteria described by Ogawa et al (40) for the identification of Kupffer cells.…”
Section: The Sinusoidal Systemmentioning
confidence: 95%
“…The endothelial cells had a few short cytoplasmic extensions into the sinusoidal lumen, smoothcoated pinocytotic vesicles at the plasma membrane, and smooth-surfaced vesicles in the cytoplasm; however, none was seen that was rich the light microscope degenerative liver changes 2Martin Feed Mills, Elmira, Ontario. and lipid accumulation have been seen in two 3Generously supplied by Monsanto Canada Ltd., species of fish exposed to PCB's (13,37). in lysosomes, that had many cytoplasmic projections, or whose cytoplasm was protuberant into the sinusoidal lumen, criteria described by Ogawa et al (40) for the identification of Kupffer cells.…”
Section: The Sinusoidal Systemmentioning
confidence: 95%
“…Because of their omnivorous feeding characteristics and association with sediments, blue crabs are exposed and may potentially accumulate significant amount of pollutants above background seawater concentrations (Nimmo et al 1975;VanderOost et al 1988). This species represents one of the most valuable fishery resources in the southern states.…”
mentioning
confidence: 99%
“…Our results found that test fish that did not show external DELT or fluctuating asymmetry had internal effects consistent with contaminant effects (100 %). Contaminants such as PCBs can have negative effects on internal organs including the liver (Nimmo et al 1975;Hansen et al 1976;Freeman et al 1982;Cleland et al 1998;Orn et al 1998). Significant occurrence of internal organ anomalies and destruction of gonadal tissues was the usual situation in Grand Calumet River reaches.…”
Section: Internal Organ Anomaliesmentioning
confidence: 95%